Mechanism of Actions, Efficacy, and Long-term Use of Steroids in Autoimmune Hemolytic Anemia (AIHA) - Yulistiani, Yulistiani; Dwiyatna, Surya; Utomo, Febriansyah Nur (Molecular and Cellular Biomedical Sciences, 2023)
Autoimmune hemolytic anemia (AIHA) is a rare condition in which autoantibodies cause the loss of red blood cells. Steroids have been used to treat several illnesses, including AIHA. For now, steroids remain as the first line of treatment for AIHA. In AIHA, especially warm AIHA (wAIHA), steroids suppress autoantibody production and downregulate Fcγ receptors' expression on monocytes to prevent hemolysis. The type of steroids chosen for first-line therapy for wAIHA in pediatrics and adults are Prednisone (Prednisolone) and Methylprednisolone. At the same time, Dexamethasone is used as an alternative treatment in AIHA. Steroids show better therapeutic outcomes in the first 2-3 weeks of administration, but the proportion of patients who remain in remission after steroid discontinuation are still quite low. Long-term administration of steroids may affect bone, blood glucose metabolism, and hypothalamic-pituitary-adrenal axis (HPAA). However, steroids which have a linear pharmacokinetic profile, intermediate-acting glucocorticoids such as Prednisone (Prednisolone) or Methylprednisolone, and also tapering dose of steroids after 2-4 weeks administration will be safe for long term use as AIHA treatment.Keywords: steroids, glucocorticoid, corticosteroid, autoimmune hemolytic anemia, AIHA, mechanism of action, efficacy